1987
DOI: 10.1126/science.3686011
|View full text |Cite
|
Sign up to set email alerts
|

Structure of a Psoralen Cross-Linked DNA in Solution by Nuclear Magnetic Resonance

Abstract: One- and two-dimensional nuclear magnetic resonance (NMR) methods were used to determine a three-dimensional model of an eight-base-pair DNA fragment (d-GGGTACCC) cross-linked with psoralen in solution. Two-dimensional nuclear Overhauser effect experiments were used to assign the spectrum and estimate distances for 171 proton pairs in the cross-linked DNA. The NMR-derived model shows a 53 degree bend into the major groove that occurs primarily at the site of drug addition and a 56 degree unwinding that spans t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
1

Year Published

1989
1989
2000
2000

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(54 citation statements)
references
References 31 publications
6
47
1
Order By: Relevance
“…Thymines in 5Ј-TpA sites of B-form duplex DNA are the preferential targets of psoralens (63,64). As judged by NMR analysis, interstrand psoralen cross-links distort the double helix of B-form DNA only slightly (65). Consistent with this conclusion, we observed that TBP was able to bind to the cross-linked substrate we prepared as efficiently as to an identical, but non-cross-linked, probe (Fig.…”
Section: Figsupporting
confidence: 77%
“…Thymines in 5Ј-TpA sites of B-form duplex DNA are the preferential targets of psoralens (63,64). As judged by NMR analysis, interstrand psoralen cross-links distort the double helix of B-form DNA only slightly (65). Consistent with this conclusion, we observed that TBP was able to bind to the cross-linked substrate we prepared as efficiently as to an identical, but non-cross-linked, probe (Fig.…”
Section: Figsupporting
confidence: 77%
“…roughly parallel to each other and to the plane of psoralen, while the modified thymines undergo important angular deformations, especially TI which is situated at the extremity. No unwinding perturbation is observed, as opposed to the results obtained by Tomic et al, also from NMR data (27). This is probably due to the location of psoralen at the extremity of the oligonucleotide in our case.…”
Section: Location Of the Psoralen Derivativecontrasting
confidence: 56%
“…As already reported (27), the covalent photo-addition of psoralen across the 5-6 double bonds of thymines 1 and 2 shifts the H6 resonances into the same region as H4', H5' and H5" resonances of sugars (Fig. 4 and Table 2).…”
Section: Location Of the Psoralen Derivativesupporting
confidence: 55%
See 1 more Smart Citation
“…[69][70][71][72] However, a kink is neither a sufficient nor a necessary determinant for damage recognition, 67,68 and destabilization of the base-stacking interactions in the vicinity of the altered site has been singled out as the common feature of all DNA modifications that are recognized as damage by the excinuclease repair machinery. 68 The nature of this destabilization in ditercalinium-and Flexi-Di-DNA complexes has already been discussed.…”
Section: Discussionmentioning
confidence: 99%